Studies of recrystallization in rhenium using positron annihilation spectroscopy. (December 2022) - Dryzek, Jerzy; Wróbel, Mirosław
Abstract: Pure rhenium exposed to cold-rolling was subjected to annealing studies using positron annihilation techniques. The recovery and recrystallization processes were observed using these techniques and they were confirmed by hardness measurement and X-ray diffraction. Using the positron diffusion trapping model the activation energy of the grain boundary migration was determined as 1.08±0.05 eV, and the recrystallization temperature was estimated to be around 950 °C. Additionally, the bulk positron lifetime in this metal determined as 98.38±0.30 ps. Graphical abstract: Image, graphical abstract